2022
DOI: 10.1038/s41598-022-08686-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole-brain white matter correlates of personality profiles predictive of subjective well-being

Abstract: We investigated the white matter correlates of personality profiles predictive of subjective well-being. Using principal component analysis to first determine the possible personality profiles onto which core personality measures would load, we subsequently searched for whole-brain white matter correlations with these profiles. We found three personality profiles that correlated with the integrity of white matter tracts. The correlates of an “optimistic” personality profile suggest (a) an intricate network for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 183 publications
(183 reference statements)
0
3
0
Order By: Relevance
“…Relating to white matter specifically, previous literature finding associations between aspects of wellbeing and structural connectivity, only reported on bilateral findings (Jung et al, 2022 ; Vitolo et al, 2022 ). Additionally, although Kotikalapudi et al ( 2022 ) reported that optimism was associated with AD in numerous tracts in the right hemisphere exclusively, their participants were mostly female and ranged from 18 to 40 years old. From a developmental perspective, a recent study reported on the FA values of the three branches of the SLF, finding a significant right lateralization in adolescents, but only in two portions of the SLF (Amemiya et al, 2021 ), whilst a longitudinal study in 9–13 year olds reported that pubertal stage was positively correlated with fiber density in the SLF-R specifically (Genc et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Relating to white matter specifically, previous literature finding associations between aspects of wellbeing and structural connectivity, only reported on bilateral findings (Jung et al, 2022 ; Vitolo et al, 2022 ). Additionally, although Kotikalapudi et al ( 2022 ) reported that optimism was associated with AD in numerous tracts in the right hemisphere exclusively, their participants were mostly female and ranged from 18 to 40 years old. From a developmental perspective, a recent study reported on the FA values of the three branches of the SLF, finding a significant right lateralization in adolescents, but only in two portions of the SLF (Amemiya et al, 2021 ), whilst a longitudinal study in 9–13 year olds reported that pubertal stage was positively correlated with fiber density in the SLF-R specifically (Genc et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…Vitolo et al ( 2022 ) measured emotion regulation and white matter microstructure, finding anomalies across tracts linking occipital, parietal, and temporal regions, whereby those with low re-appraisal had increased mean diffusivity in clusters within the superior longitudinal fasciculus (SLF), superior corona radiata (SCR) and anterior uncinate fasciculus (UF). Kotikalapudi et al ( 2022 ) investigated personality profiles that may be predictive of wellbeing and the potential relationships with white matter. They found that optimism was positively associated with AD values exclusively in the right hemisphere, and specifically within the anterior cingulum bundle (CNG), anterior corpus callosum (CC genu), anterior thalamic radiation (ATR), corticospinal tract (CST—which had the strongest finding relating to cluster size), SLF, and UF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation